2022
DOI: 10.3389/fnmol.2022.1056966
|View full text |Cite
|
Sign up to set email alerts
|

Is transcranial direct current stimulation beneficial for treating pain, depression, and anxiety symptoms in patients with chronic pain? A systematic review and meta-analysis

Abstract: BackgroundChronic pain is often accompanied by emotional dysfunction. Transcranial direct current stimulation (tDCS) has been used for reducing pain, depressive and anxiety symptoms in chronic pain patients, but its therapeutic effect remains unknown.ObjectivesTo ascertain the treatment effect of tDCS on pain, depression, and anxiety symptoms of patients suffering from chronic pain, and potential factors that modulate the effectiveness of tDCS.MethodsLiterature search was performed on PubMed, Embase, Web of Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 97 publications
0
9
1
Order By: Relevance
“…They included 27 randomized controlled trials with a total of 1,015 participants who received tDCS or sham stimulation for various chronic pain conditions. They found that tDCS was significantly more effective than sham stimulation in reducing short-term pain intensity (SMD = -0.43, 95% CI = -0.75 to -0.12), short-term and middle-term depression (SMD = -0.31, 95% CI = -0.47 to -0.14, and SMD = -0.35, 95% CI = -0.58 to -0.11), and anxiety scores (SMD = -0.36, 95% CI = -0.58 to -0.14) in patients with chronic pain, but longer-lasting effects were not observed [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…They included 27 randomized controlled trials with a total of 1,015 participants who received tDCS or sham stimulation for various chronic pain conditions. They found that tDCS was significantly more effective than sham stimulation in reducing short-term pain intensity (SMD = -0.43, 95% CI = -0.75 to -0.12), short-term and middle-term depression (SMD = -0.31, 95% CI = -0.47 to -0.14, and SMD = -0.35, 95% CI = -0.58 to -0.11), and anxiety scores (SMD = -0.36, 95% CI = -0.58 to -0.14) in patients with chronic pain, but longer-lasting effects were not observed [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In patients undergoing total knee arthroplasty, tDCS of PFC, but not M1, reduced opioid use in the three-day period following surgery (Borckardt et al, 2017), which strengthens the clinical relevance of PFC stimulation as an adjunctive therapy for pharmacological treatment of surgical pain. However, discrepancies over the effectiveness of tDCS remain as systematic reviews and meta-analysis report limited evidence for a pain reducing effect of tDCS targeted to the PFC in fibromyalgia or neuropathic pain (Zhu et al, 2017;Knotkova et al, 2021;Wen et al, 2022), which means improvements are needed in this area.…”
Section: Non-invasive Brain Stimulationmentioning
confidence: 99%
“…This suggests that patients with knee osteoarthritis may be more receptive to tDCS with additional therapy when the treatment plan is of moderate length [37,43]. A recent review supported the selective treatment effects of tDCS, demonstrating that the groups receiving 5-10 sessions of tDCS showed a significant improvement in chronic pain [44].…”
Section: Knee Painmentioning
confidence: 99%